Changes in white matter microstructure in the brain of patients with inflammatory bowel disease are associated with abdominal pain - Zhang, Lingqin; Tang, Wuli; Yang, Ling; Wu, Xinyan; Deng, Xin; Yu, Li; Liu, Yan; Li, Kang (Frontiers in Neuroscience, 2025)
IntroductionIn recent years, interest in the brain-gut axis has increased, and interactions between the brain and the gut may be closely related to recurrent clinical symptoms in patients with inflammatory bowel disease. We aimed to investigate the changes in white matter microstructure in the brain of patients and their relationships with clinical symptoms.MethodsA total of 96 patients with inflammatory bowel disease and 47 healthy controls were recruited for this study. All participants underwent diffusion tensor imaging of the brain. Tract-based spatial statistics were used to compare differences in brain white matter microstructure between the patients and healthy controls. Partial least squares correlation analysis was conducted to examine the relationships between changes in white matter microstructure in patients and their clinical symptoms.ResultsCompared with healthy controls, patients with inflammatory bowel disease presented decreased mean diffusivity, axial diffusivity, and radial diffusivity in multiple white matter regions (p < 0.05, corrected). Further analysis revealed that patients with ulcerative colitis did not present significant differences in brain white matter microstructure (p > 0.05), whereas patients with Crohn’s disease presented abnormalities in multiple regions, including the corticospinal tracts, corona radiata, and corpus callosum. Multivariate analysis revealed that altered white matter in the brains of patients with inflammatory bowel disease was mainly positively correlated with pain-related negative emotions, such as scores from the fear of pain questionnaire and the pain anxiety symptoms scale.ConclusionsIn patients with inflammatory bowel disease, particularly those with Crohn’s disease, alterations in the white matter microstructure that are primarily involved in pain processing have been observed.